Electric energy : an introduction - El-Sharkawi, Mohamed A (Boca Raton, FL : Taylor and Francis, 2012)
"Along with the standard topics of power electronics and electromechanical conversion, this popular text covers energy resources, power plants, environmental impacts of power generation, power system operation, renewable energy, and electrical safety. Focusing on issues encountered daily in practice, the author includes examples based on real systems and data. Now in color, this third edition offers new and expanded coverage on the failure modes of nuclear power plants, interface and integration issues, stray voltage and impulse shocks, the circuits in wind and solar systems, and smart grid technology"--
Transformer 11.4.2 Transformer Bank 11.5 Actual Transformer 11.5.1 Analysis of Actual Transformer 11.5.2 Transformer Efficiency 11.5.3 Voltage Regulation Exercises Chapter 12 Electric Machines 12.1 Rotating Magnetic Field 12.2 Rotating Induction Motor 12.2.1 Rotation of Induction Motor 12.2.2 Equivalent Circuit of Induction Motor 12.2.3 Power Analysis 12.2.4 Speed-Torque Relationship 12.2.5 Starting Torque and Starting Current 12.2.6 Maximum Torque 12.2.7 Starting Methods 12.2.7.1 Voltage Reduction 12.2.7.2 Insertion of Resistance 12.3 Linear Induction Motor 12.3.1 Wheeled Linear Induction Motor 12.3.2 Magnetically Levitated Induction Motor 12.4 Induction Generator 12.5 Synchronous Generator 12.5.1 Synchronous Generator Connected to Infinite Bus 12.5.1.1 Power of Synchronous Generator 12.5.2 Synchronous Generator Connected to Infinite Bus through a Transmission Line 12.5.3 Increase Transmission Capacity 12.5.3.1 Increasing Transmission Capacity by Using Series Capacitor 12.5.3.2 Increasing Transmission Capacity by Using Parallel Lines 12.6 Synchronous Motor 12.6.1 Power of Synchronous Motor 12.6.2 Reactive Power Control and Synchronous Condenser 12.6.3 Motor Torque 12.7 Direct Current Motor 12.7.1 Theory of Operation of DC Motor 12.7.2 Starting of DC Motor 12.7.3 Speed Control of DC Motor 12.8 Stepper Motor 12.8.1 Variable Reluctance Stepper Motor 12.8.2 Permanent Magnet Stepper Motor 12.8.3 Hybrid Stepper Motor 12.8.4 Holding State of Stepper Motor 12.8.5 Rotating Stepper Motor 12.9 Single-Phase Motors 12.9.1 Split-Phase Motors 12.9.2 Capacitor Starting Motors 12.9.3 Shaded-Pole Motors Exercises Chapter 13 Power Quality 13.1 Voltage Problems 13.1.1 Voltage Flickers 13.1.2 Voltage Sag 13.2 Harmonic Problems 13.2.1 Harmonic Distortion of Electric Loads 13.2.2 Resonance due to Harmonics 13.2.3 Effect of Harmonics on Transmission Lines and Cables 13.2.4 Effect of Harmonics on Capacitor Banks 13.2.5 Effect of Harmonics on Electric Machines 13.2.6 Effect of Harmonics on Electric Power 13.2.7 Effect of Harmonics on Communications Exercises Chapter 14 Power Grid and Blackouts 14.1 Topology of Power Systems 14.1.1 Enhancing Power System Reliability by Adding Transmission Lines 14.1.2 Enhancing Power System Reliability by Adding Generation 14.2 Analysis of Power Networks 14.3 Electric Energy Demand 14.4 Trading Electric Energy 14.5 World Wide Web of Power 14.6 Anatomy of Blackouts 14.6.1 Balance of Electric Power 14.6.2 Balance of Electrical and Mechanical Powers 14.6.2.1 Control Actions for Decreased Demand 14.6.2.2 Control Actions for Increased Demand 14.7 Blackout Scenarios 14.7.1 Great Northeast Blackout of 1965 14.7.2 Great Blackout of 1977 14.7.3 Great Blackout of 2003 Exercises Chapter 15 Future Power Systems 15.1 Smart Grid 15.1.1 Intelligent Monitoring 15.1.2 Smart House 15.1.3 Self-Diagnosis and Self-Healing 15.2 Electric and Hybrid Electric Vehicles 15.3 Alternative Resources 15.4 Less Polluting Power Plants 15.5 Distributed Generation 15.6 Power Electronics 15.7 Enhanced Reliability 15.8 Intelligent Operation, Maintenance, and Training 15.9 Space Power Plants Exercises Appendix A Units and Symbols Appendix B Conversions Appendix C Key Parameters Appendix D Inductors Appendix E Key Integrals Index
Includes bibliographical references and index
Keywords: Power electronics; Electric power systems